The Avalon Ladies Scrapbooking Society : a novel - Gee, Darien (Ballantine Books, 2013)
"At Madeline's Tea Salon, the cozy hub of the Avalon community, local residents scrapbook their memories and make new ones. But across town, other Avalonians are struggling to free themselves of the past ... Enter Bettie Shelton, the irascible founder of the Avalon Ladies Scrapbooking Society. Under Bettie's guidance, even the most reluctant of Avalon's residents come to terms with their past and make bold decisions about their future. But when the group receives unexpected news about their steadfast leader, they must pull together to create something truly memorable."--Provided by publisher.